Bupropion increases cerebral activation in auditory affective processing: A randomized controlled fMRI study. (1st April 2021) - Hama, Tomoko; Koeda, Michihiko; Ikeda, Yumiko; Tateno, Amane; Kawara, Tokuhiro; Suzuki, Hidenori; Okubo, Yoshiro
Highlights: We studied the effect of bupropion on brain activation by auditory emotional task. Bupropion increased the brain activation in emotional circuits. In particular, brain activation was increased during positive emotion recognition. The results may reflect the neural basis of the therapeutic effect of bupropion. Abstract: Introduction: Bupropion is an antidepressant with less possibility to give rise to emotional blunting as side effect, and it also acts on improving negative self-recognition in a depressive state. Previous neuroimaging studies indicated a change in brain function by facial expression as an effect of antidepressants. As well as facial expression, vocal affective processing is essential for accurately recognizing another's feelings, but to our knowledge, no study has investigated whether bupropion affects the cerebral function of recognition of auditory affective processing. In this study, we aimed to investigate the acute effect of bupropion on cerebral response to vocal affective processing. Methods: Sixteen healthy volunteers (male = 8) participated in this study. With a randomized placebo-controlled within-subject trial, two series of fMRI scans, using either placebo or bupropion (150 mg), were examined. An auditory emotional valence judgement task was performed during fMRI scanning. The acute effects of bupropion on cerebral activation in the emotional circuit and behavioral performance during emotional processing were analyzed. Results: Compared with placebo, bupropion caused a significantly greater activation of emotional voices in the left insula and right superior temporal gyrus, whereas the amygdala was not activated. By bupropion, a significantly greater activation of the positive emotional circuit was observed at the superior temporal gyrus and middle frontal gyrus. As for behavioral performance, no significant difference was observed between placebo and bupropion. Conclusions: Our findings suggest that bupropion enhances the cerebral response to affective processing, especially positive emotional vocalizations, indicating a possible mechanism underlying the therapeutic effects for patients with depression.